Interaction of curcumin nanoformulations with human plasma proteins and erythrocytes - Yallapu MM (Dove Medical Press, 2011)
Murali Mohan Yallapu1, Mara C Ebeling1, Neeraj Chauhan1,3, Meena Jaggi1-3, Subhash C Chauhan1-31Cancer Biology Research Center, Sanford Research, 2Department of Obstetrics and Gynecology, 3Basic Biomedical Science Division, Sanford School of Medicine, University of South Dakota, Sioux Falls, SDBackground: Recent studies report curcumin nanoformulation(s) based on polylactic-co-glycolic acid (PLGA), ß-cyclodextrin, cellulose, nanogel, and dendrimers to have anticancer potential. However, no comparative data are currently available for the interaction of curcumin nanoformulations with blood proteins and erythrocytes. The objective of this study was to examine the interaction of curcumin nanoformulations with cancer cells, serum proteins, and human red blood cells, and to assess their potential application for in vivo preclinical and clinical studies.Methods: The cellular uptake of curcumin nanoformulations was assessed by measuring curcumin levels in cancer cells using ultraviolet-visible spectrophotometry. Protein interaction studies were conducted using particle size analysis, zeta potential, and Western blot techniques. Curcumin nanoformulations were incubated with human red blood cells to evaluate their acute toxicity and hemocompatibility.Results: Cellular uptake of curcumin nanoformulations by cancer cells demonstrated preferential uptake versus free curcumin. Particle sizes and zeta potentials of curucumin nanoformulations were varied after human serum albumin adsorption. A remarkable capacity of the dendrimer curcumin nanoformulation to bind to plasma protein was observed, while the other formulations showed minimal binding capacity. Dendrimer curcumin nanoformulations also showed higher toxicity to red blood cells compared with the other curcumin nanoformulations.Conclusion: PLGA and nanogel curcumin nanoformulations appear to be very compatible with erythrocytes and have low serum protein binding characteristics, which suggests that they may be suitable for application in the treatment of malignancy. These findings advance our understanding of the characteristics of curcumin nanoformulations, a necessary component in harnessing and implementing improved in vivo effects of curcumin.Keywords: nanoparticle, curcumin, chemotherapy, cellular uptake, protein binding, hemocompatibility